2001
DOI: 10.1089/10807680152729248
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Bioavailability of Ciprofloxacin in Sustained Release Formulations

Abstract: A novel sustained release delivery system of ciprofloxacin for the eye was developed. The system consists of a viscosity enhancer (carbopol gel or hydroxypropylmethylcellulose solution) plus a penetration enhancer (dodecylmaltoside) to overcome penetration barriers and loss due to wash-out and thus achieve the desired ciprofloxacin ocular absorption. The present studies were designed to assess the ocular penetration and bioavailability of ciprofloxacin in sustained release formulations. In vitro studies in rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…These results correlates with permeability coefficients published in earlier studies. The permeability coefficient of ciprofloxacin in rabbit sclera was measured to be 1.88 ± 0.617 × 10 -5 cm/sec (74). Results for glucose diffusion are in good agreement with that for human sclera (75).…”
Section: Resultssupporting
confidence: 70%
“…These results correlates with permeability coefficients published in earlier studies. The permeability coefficient of ciprofloxacin in rabbit sclera was measured to be 1.88 ± 0.617 × 10 -5 cm/sec (74). Results for glucose diffusion are in good agreement with that for human sclera (75).…”
Section: Resultssupporting
confidence: 70%
“…This is attributed to the structural complexity of corneal layers. Inclusion of penetration enhancers (e.g., benzalkonium chloride, ethylenediaminetetraacetic acid, Tween 20, Brij ® 35, and dodecylmaltoside [29,30]), Cyclodextrins [31], and dendrimers [32,33] in ocular formulations has been reported to increase corneal penetration of the tested antibacterial agents [34].…”
Section: General Considerations For Designing Ocular Drug Delivery Fomentioning
confidence: 99%
“…The system was based on the use of carbopol gel or hydroxypropyl methyl cellulose as a viscosity enhancing agent in addition to dodecylmaltoside as a penetration enhancer to achieve the desired ocular absorption of ciprofloxacin. The carried out in vivo bioavailability studies showed that the sustained release formulations delivered 10-fold more drug into the aqueous humor than the standard solution formulation [19].…”
Section: Fig 6: Relationship Between the Amount Of Sd2 As A Matrix (mentioning
confidence: 99%